Analisis Kinerja Kantor Kesehatan Pelabuhan Poso - Usu, Abdul Rahmat; Sulaeman, Sulaeman (Gorontalo Accounting Journal, 2022)
Public sector organizations must be able to carry out good performance for accountability to the community. This study aims to determine the performance of the Poso Port Health Office with a value for money approach. This study uses secondary data, during the 2015-2020 period. The data analysis used in this research is qualitative data analysis and quantitative data analysis. The results of the analysis obtained according to the principle of value for money, namely the economic criteria showed a ratio of 90%-100% which according to economic performance was carried out. While the efficiency criteria of the Poso port health office get a result of 7%-30% which means that there is a very high efficiency performance. The last criterion is the effectiveness criteria, the organization carries out performance effectively, as shown from the results of the calculation of the ratio above 100%.